Measuring Factors influencing Work Engagement among Millennials in Malaysian Organization - Shahruddin, Shafiq; Azma, Mohd Azrul; Arifin, Muhammad Aiman (Journal of Entrepreneurship, Business and Economics; Vol 11 No 2 (2023), 2023)
This study addresses a pressing issue in the contemporary global economy by examining the critical relationship between work engagement and the quality of work-life among millennial employees, with a specific focus on the Y generation. In an era of economic volatility, the sustainability of employee engagement has emerged as a paramount concern for various industries. Research has shown that millennial employees with low or no work engagement are highly inclined to leave their organizations within a year. To explore this nexus, the study adapted Walton's quality of the work-life model and integrated it with the JD-R Theory. Therefore, study's objective is to determine the impact of quality of work-life on work engagement, with a particular emphasis on the role of psychological capital as a mediator. Employing a mixed-mode research approach, the study will conducted within the organizational landscape of Malaysia, utilizing online platforms. This research contributes significantly to the ongoing discourse on work engagement by delving deeper into the interconnected realms of Quality of Work-Life, Work Engagement, and Psychological Capital among younger employees, thereby offering insights crucial for sustaining economic vitality. As a move forward, this study paves the way for future investigations into this conceptual domain. Research paper Keywords: Work Engagement; Quality of Work-Life; Psychological Capital; Young Employees Reference to this paper should be made as follows: Shahruddin, S., Azman, M. A.., & Arifin, M. A. (2023). Measuring Factors influencing Work Engagement among Millennials in Malaysian Organization. Journal of Entrepreneurship, Business and Economics , 11 (2), 53–80.